2007
DOI: 10.1590/s1519-566x2007000600019
|View full text |Cite
|
Sign up to set email alerts
|

Estudo preliminar da preferência alimentar de Nyssomyia neivai (Pinto) e Nyssomyia whitmani (Antunes & Coutinho) (Diptera: Psychodidae) em área rural do Paraná

Abstract: Due to the importance of sandflies in the American cutaneous leishmaniasis epidemiology, we investigated the feeding preference of sandflies related to domestic animals common in domiciliary environments in endemic rural areas, where this disease occurs. The sandflies were collected with Falcão light traps, installed in cages, each one containing one domestic animal kind (pig, dog, rabbit or chicken), in Recanto Marista, in Doutor Camargo municipality. Forty five collections were made, totaling 135h of collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
2
11
0
4
Order By: Relevance
“…The high frequency of these species corroborates the findings of other endemic regions of Brazil (2). The high frequency of L. (V.) braziliensis coincides with the frequent finding of L. whitmani, a sand fly that can transmit this parasite to humans and domestic mammals (12,13). In contrast, the low frequency of L. (L).…”
supporting
confidence: 67%
“…The high frequency of these species corroborates the findings of other endemic regions of Brazil (2). The high frequency of L. (V.) braziliensis coincides with the frequent finding of L. whitmani, a sand fly that can transmit this parasite to humans and domestic mammals (12,13). In contrast, the low frequency of L. (L).…”
supporting
confidence: 67%
“…In other words, the presence of animal species different from rats was a protection factor against leishmaniosis in rats (OR= 0.01273 to 0.8341). A study on Nyssomyia neivai species broadly found in Paraná State (MEMBRIVE et al, 2004;DIAS-SVERSUTTI et al, 2007;SILVA et al, 2008;CERINO et al, 2009;CRUZ et al, 2013;MELO et al, 2013), performed in Ribeira Valley São Paulo State, examined 988 engorged females, and no rat blood was detected in the phlebotomines (MARASSÁ et al, 2013). According to Dias-Sversutti et al (2007), N. neivai and N. whitmani are opportunists and probably adjust their feeding habits based on the availability of hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatheca width less than twice that of the individual sperm duct, this being as long as the common duct (Fig 12) ……………….……………............…… E. rupicola Width of spermatheca at least three times that of the individual duct, this being shorter than the common duct (Fig 19) So far, we have information that the rupicola series is restricted to Brazil and is limited to the Atlantic forest domain. Evandromyia correalimai is the species with the widest known distribution, including interior areas of the Southeastern (Forattini et al 1976, Galati et al 2010 and Southern regions (Martins et al 1970, 1978, Gomes & Galati 1977, Aguiar et al 1989, Dias et al 1997, Silva & Grunewald 1999, Luz et al 2000, Massafera et al 2005, Dias-Sversutti et al 2007, Silva et al 2008. Evandromyia rupicola is restricted to the Southeastern region, in the mountainous region of eastern Minas Gerais state (Mayrink et al 1979), Rio de Janeiro state (Martins et al 1962, 1978, Aguiar et al 1985, Afonso et al 2007 and in the coastal area of São Paulo state (Condino 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Bar = 100 µm. (Forattini et al 1976, Galati et al 2010, PARANÁ state (Apucarana, Arapongas, Borrazópolis, Bandeirantes, Curitiba, Doutor Camargo, Jacarezinho, Jussara, Londrina and Marumbi municipalities (Martins et al 1970, 1978, Gomes & Galati 1977, Aguiar et al 1989, Luz et al 2000, Massafera et al 2005, Dias-Sversutti et al 2007, Silva et al 2008 and RIO GRANDE DO SUL (Derrubadas and Tenente Portela municipalities) (Dias et al 1997, Silva & Grunewald 1999. Evandromyia rupicola: MINAS GERAIS -Caratinga municipality (Mayrink et al 1979), RIO DE JANEIRO state -Magé, Petrópolis, Resende/Itatiaia municipalities (Martins et al 1962, 1978, Aguiar et al 1985, Afonso et al 2007 and SÃO PAULO state -Ilhabela and Ubatuba municipalities (Condino 2007 …”
Section: Description Of the Female Of Evandromyia Rupicola With A Revmentioning
confidence: 99%